Analysis of the Implementation of Gerakan Ayo Sekolah Movement in Improving the Human Development Index in Ketapang District - Jatmiko, Heri; Asriati, Nuraini; Syamsuri, Syamsuri; Ulfa, Maria; Achmadi, Achmadi (Education Achievement: Journal of Science and Research, 2024)
The research analyzes the implementation of Gerakan Ayo Sekolah (GAS) Program in dealing with Out-of-school children (ATS) and Out of School Adults (DTS) in Ketapang Regency. Carried out in four sub-districts, namely Matan Hilir Utara, Muara Pawan, Delta Pawan, and Benua Kayong. This research method uses qualitative research, the results of the analysis show an average of strengths and weaknesses of 3.2, and opportunities and threats of 3. IFAS (Internal Factor Analysis Summary) value is 2.81 and EFAS (External Factor Analysis Summary) is 2.79 placing GAS (Gerakan Ayo Sekolah) in a position of growth. Data shows an increase in the HDI (Human Development Index) from 67.92% (2021) to 68.68% (2023), associated with an increase in the average length of schooling through GAS (Gerakan Ayo Sekolah). A total of 54 individuals returned to school, both formal and non-formal. SWOT analysis integrates internal and external factors towards the implementation of GAS (Gerakan Ayo Sekolah). Matrix IE (Internal External) shows the growth potential of GAS (Gerakan Ayo Sekolah) in increasing the HDI (Human Development Index), with the intersection point in quadrant V, indicating the potential of GAS (Gerakan Ayo Sekolah) in increasing the HDI (Human Development Index) through efforts to overcome dropping out of school and preventing vulnerable children from dropping out of school.